PERLINDUNGAN HUKUM DEBITUR DALAM KONTRAK PEMBIAYAAN KONSUMEN DIKOTA PALU - Rina, Rina (Katalogis, 2015)
This study reviews How Legal Protection for debtors in financial contracts Consumers in Palu? And How do legal settlement in the event of default by the parties to the consumer finance ?. The purpose of this study was to determine and assess the legal protection for debtors in consumer financing contracts in the city of Palu, as well as about the legal settlement to do in the event of default by the parties to the consumer financing. Research using this type of juridical empirical research using descriptive analysis method with approach Regulations Act and sociological approach which aims to describe a systematic, factual and accurate information about the implementation of consumer financing agreement with the Fiduciary. The data used in this research is primary data obtained by means of an inventory of documents through library and field study that is by interview , made ​​questionnaires filled by the respondents .        The study concluded that in protecting consumers in the financing contract is by banning the inclusion of standard clause in every contract of consumer financing in accordance with the rules of Article 18 of Law No. 8 of 1999 on Consumer Protection. Regarding defaults that occurred in consumer financing agreement between the consumer with Financing Company is the delay in arrears monthly installments are not in accordance with the contract. The sanction of debtor default is the withdrawal of fiduciary security object, but the execution must comply with regulations that register objects fiduciary Online at the Directorate General Law Administration of the Ministry of Justice and Human Rights of the Republic of Indonesia. Researchers suggest that the need for oversight and review of the government regarding the standard contract made by the finance company. The Government should further reinforce the regulation of consumer financing agreement where the latter for the perpetrators of violations of consumer financing given strict sanctions.